2003
DOI: 10.1007/978-3-540-45189-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Formalizing Rework in Software Processes

Abstract: Abstract. This paper indicates how effective software-process programming languages can lead to improved understandings of critical software processes, as well as improved process performance. In this paper we study the commonly mentioned, but seldom defined, rework process. We note that rework is generally understood to be a major software development activity, but note that it is poorly defined and understood. In this paper we use the vehicle of softwareprocess programming to elucidate the nature of this typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…In earlier work [1] we suggested that rework can be modeled as re-invocation of one or more development activities that had been carried out previously, but now must be carried out in a context different from the original execution, where a context is any aspect of the process step's dynamic, run-time environment (e.g. input parameters, resources, or personnel employed) that can cause the step to be carried out differently or produce a different result.…”
Section: Introductionmentioning
confidence: 93%
“…In earlier work [1] we suggested that rework can be modeled as re-invocation of one or more development activities that had been carried out previously, but now must be carried out in a context different from the original execution, where a context is any aspect of the process step's dynamic, run-time environment (e.g. input parameters, resources, or personnel employed) that can cause the step to be carried out differently or produce a different result.…”
Section: Introductionmentioning
confidence: 93%
“…Suppose, however, that the user fixes the compilation error but the unit test still reports failure, thus causing another round of rework driven by a new instance of UnitTestFailureException. Figure 4 characterizes part of the DDG abstraction in this situation and covers its key features 1 . The diagram consists of two different kinds of nodes.…”
Section: Context In Exception-driven Reworkmentioning
confidence: 99%
“…The round one stands for the leaf step execution and the rectangle one describes the data object. The exception data object is shown in brown or a deeper 1 Figure 4 is a simplified representation of the DDG that is actually generated automatically. The actual DDG that would be generated by this process execution would contain more features and details that represent such execution aspects as scoping.…”
Section: Context In Exception-driven Reworkmentioning
confidence: 99%
See 2 more Smart Citations